The Influence Of Online Customer Reviews, Online Customer Ratings And Price Perceptions On Decisions To Purchase Bostanten Products At Shopee - Rambe, Yasmini Harjani; Rachmad, Ferizal (InJEBA : International Journal of Economics, Business and Accounting, 2025)
Purchasing decisions are individual actions involved in choosing options to obtain a product provided by the seller. This research aims to determine the influence of online customer reviews, online customer ratings and price perceptions on purchasing decisions for Bostanten products at Shopee by students from Tuah Madani District, Pekanbaru. This type of research is quantitative with a sample size of 100 respondents from Tuah Madani District Students, Pekanbaru who bought Bostanten products at Shopee. Determination of samples using Le.me.show with sampling procedures using purposive techniques. Sampling. The method was analyzed using the SPSS program. The data source used is primary data. The results of this research show that Online Customer Reviews, Online Customer Ratings and Price Perceptions have a positive effect on Purchasing Decisions. This means that students show that the better the reviews and ratings the product receives, as well as the more positive the consumer's perception of price, the greater the student's likelihood of making a purchase.